Damage development of a woven SiCf/SiC composite during multi-step fatigue tests at room temperature. Issue 14 (1st October 2020) - Xue, Yudong; Hu, Jianbao; Zhou, Haijun; Li, Longbin; Shan, Qingliang; Kan, Yanmei; Gao, Le; Dong, Shaoming
Abstract: The monotonic tensile and multi-step fatigue tests of 2D woven SiCf /SiC composite were performed to explore the damage development, respectively. The acoustic emission-based technique was used to analyze the damage state and select the peak stresses for fatigue tests. The damage evolution after specific mechanical tests was characterized by optical microscopy and scanning electron microscopy. Cracks are prone to occur in the vicinity of flaws and boundaries of different matrix components under relatively low fatigue stress. The cyclic fatigue stress can do much harm to the interfaces and facilitate the interfacial debonding. The damage characteristics of five types of cracking, fiber breakage and pull-out, and interfacial debonding of the composite after specific mechanical tests are concluded and discussed in detail, which can offer help for deeper analysis of the oxidation mechanism in service and more reasonable design of SiCf /SiC composite.